(untitled) (Psychology Travelogs, 2025)
In today’s world, the importance of mental health and emotional stability is particularly significant, especially amid social changes and crises. Research in this area shows that the behavioral strategies employed by individuals prone to aggression can profoundly impact their lives and the lives of those around them. The primary aim of this article is to analyze the behavioral strategies of perpetrators and their correction through psychological interventions. The article also presents contemporary studies by Ukrainian scientists on the behavioral characteristics of perpetrators and ways to correct dysfunctional patterns. The results indicate that the correction of behavioral strategies can be achieved through targeted interventions aimed at developing emotional awareness, improving communication skills, and fostering constructive behavior models. One of the key recommendations is the implementation of training programs that provide perpetrators with the opportunity to understand the reasons behind their aggressive actions and learn alternative responses to conflict situations. The procedure for psychological interventions is outlined in a general framework. It comprises three phases: preliminary assessment, direct intervention, and final evaluation. Additionally, emphasis is placed on the importance of family therapy and social support in the process of changing the behavior of aggressors. The study demonstrates that positive changes are possible through a comprehensive approach to correcting aggressive behavior, which takes into account the individual characteristics of the person and their social environment. The results outlined in this work can be utilized by professionals to develop effective psychotherapy and social correction and rehabilitation programs. Thus, the findings of this research have practical significance for psychologists, social workers, and educators working with individuals prone to aggression.